2016
DOI: 10.1038/ncomms11403
|View full text |Cite
|
Sign up to set email alerts
|

Nonadditivity of critical Casimir forces

Abstract: In soft condensed matter physics, effective interactions often emerge due to the spatial confinement of fluctuating fields. For instance, microscopic particles dissolved in a binary liquid mixture are subject to critical Casimir forces whenever their surfaces confine the thermal fluctuations of the order parameter of the solvent close to its critical demixing point. These forces are theoretically predicted to be nonadditive on the scale set by the bulk correlation length of the fluctuations. Here we provide di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
107
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 48 publications
9
107
0
Order By: Relevance
“…Adjusting the parameters of the theoretical potential, it is possible to match the experimental distribution P eq (r) at t = 0. By doing so, we have obtained, for each value of ∆T , the correlation length ξ of the order parameter fluctuations [9] and the Debye screening length ℓ D of the electrostatic interaction as fit parameters. Specifically, we adopt for V C the theoretical prediction…”
mentioning
confidence: 99%
“…Adjusting the parameters of the theoretical potential, it is possible to match the experimental distribution P eq (r) at t = 0. By doing so, we have obtained, for each value of ∆T , the correlation length ξ of the order parameter fluctuations [9] and the Debye screening length ℓ D of the electrostatic interaction as fit parameters. Specifically, we adopt for V C the theoretical prediction…”
mentioning
confidence: 99%
“…In Ref. [39], using a system of three optically trapped [40] spherical colloidal particles, immersed in a critical binary mixture, the authors demonstrated experimentally the theoretically predicted nonadditivity of the fluctuation-induced interactions. Other experimental setups which exploit a sphere-plate or sphere-sphere configurations immersed in a critical fluid include the interaction of spherical colloids with chemically patterned substrates [41,42] which theoretical description is discussed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…These media will enhance or reduce the vdW potential via manybody interactions [24,25]. Note that evidence for threebody dispersion forces has recently been found for the critical Casimir effect [26].…”
mentioning
confidence: 99%